Effects of Ginger (Zingiber officinale) Oil on Growth Performance and Microbial Population of Broiler Ross 308 - Shanoon, Ammar K.; Jassim, Mahdi S.; Amin, Qana H.; Ezaddin, Ilhaam N. (International Journal of Poultry Science, 2012)
An experiment was conducted at the University of Kirkuk, poultry farm of college of agriculture department of animal science to evaluate the effect of ginger oil on growth performance and microbial population of broiler chickens. Two hundred male and female day old chicks of Ross308 were arranged in a complete random design experiment and allotted to one of four treatments doses 0 (Control),10mg/kg/day (T1), 20mg/kg/day (T2) and 40mg/kg/day (T3). The trial lasted for seven weeks and there were no differences in feed intake, body weight gain and the feed conversion ratio among the birds, All organs weight and carcass characteristics were not affected by the treatments, except for a decrease (P